Condicionamento fisiológico de sementes de tabaco - Oliveira, Ariadne Santos (2016)
The desuniformity maturation of fruits and tobacco seeds have led the seed industry to use techniques such as priming, which enables to greater uniformity and speed of germination, by regeneration of the cell membrane system. Several factors may affect the physiological conditioning, such as the weather and the environment in which the treatment is performed, in addition to the initial quality of the seed lots. The use of ascorbic acid as a conditioning agent is advantageous because it is soluble in water and involved in different cellular processes, including cell division and restructuring membranes. The KNO3 can act as an additional source of potassium and nitrogen during germination, improving the seed quality. To evaluate the effect of different solutes, periods and forms of conditioning on the physiological quality of seeds were used three lots of tobacco seeds of the cultivar CSC 4703. In experiment 1, the seeds were submitted to priming in aerated solution varying the period (12, 24 and 36 hours) of conditioning, the ascorbic acid concentration [0 (hydropriming), 50, 75 and 100 mg.L-1 ] and three lots of seeds. In experiment 2 the seeds were submitted to priming in aerated solution varying the period (12, 24 and 36 hours) of conditioning, the KNO3 concentration [0 (hydropriming), -0.5; -1.0 And -1.5 MPa) and three seed lots. After the treatments, the seeds were washed in water and dried at 30 °C to return to the initial moisture. The seed quality was evaluated by germination, first count, germination speed index, initial emergency stand, emergence percentage and emergence speed index. It was concluded in experiment 1 the hydropriming improves germination and increases the vigor of tobacco seeds. In experiment 2, the conditioning with KNO3 solution adjusted to -1.0 MPa for 24 or -0.5 MPa for 36 hours promotes increments in the vigor of tobacco seeds. Tobacco seeds with lower quality respond better to physiological conditioning.